THE INFLUENCE OF SYSTEM QUALITY, INFORMATION QUALITY, SERVICE QUALITY, AND PERCEIVED USEFULNESS ON USER SATISFACTION(Empirical Study on Village Credit Institutions in Denpasar City) - Ni Made Meyfia Handayani; Dodik Ariyanto (Adisam Publisher, 2025)
The use of a quality accounting information system (AIS) in Village Credit Institutions (LPD) in Denpasar City is essential to improve work efficiency and user satisfaction in processing financial data. This study aims to examine the influence of system quality, information quality, service quality, and perceived usefulness on user satisfaction of AIS in LPDs in Denpasar. A total of 140 questionnaire responses were collected from LPD employees using a non-probability purposive sampling method and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that system quality, information quality, service quality, and perceived usefulness all have a significant influence on user satisfaction.